Fostering Descriptive Power (Analytic Teaching, 1985)
Introduction:  Perception is fascinating and is inextricably bound up with all levels and kinds of thinking.  Perceptual knowledge, descriptive data, serves as raw material for any and all processing operations.  Certainly all kinds of constructing and processing operations await, e.g., imagining, describing, generalizing, comparing, day-dreaming, thousands of kinds.  The mind is constantly at work with its symbols, such as images and language, formulating and focusing percepts out of sensory stimuli and then making thought and feeling constructs.